Mathematic Problem Solving Abilities Based on Students' Self-Efficacy By Mmp Learning The Mic Approach With Local Culture - Zubaedi, Muhammad Fakqih; Masrukan, Masrukan; Dwidayati, Nur Karomah (Unnes Journal of Mathematics Education Research, 2021)
Problem-solving ability is the ability to solve mathematical problems and is one of the abilities that students must have in order to be skilled in working on math problems. There are factors that support student success in solving problems, including self-efficacy. This study aims to describe the problem solving abilities of students who have high, moderate, high self-efficacy and low seen from the dimensions of magnitude, strength, and generality in mathematics learning with the MMP model with the MiC approach with local cultural nuances.. This research uses a mixed method research type with a concurrent embedded design. Based on the three stages of learning quality, MMP learning with the MiC approach to local culture nuances is quality learning. In the problem solving aspect, students with high self-efficacy were able to understand problems, plan problem solving, implement problem solving plans, and re-examine them with true and complete. Students with moderate self-efficacy are able to understand problems, plan problem solving, but are less able to carry out problem-solving plans and re-check. Students with low self-efficacy are able to understand problems and plan problem solving correctly but incomplete, inadequate in implementing problem-solving plans, and in rechecking, unable to use other methods.